Internal boundary and religious conflicts: the problems of national integration in post- colonial Nigeria - Ibiang O Okoi (Center for Humanities and Innovation Studies, 2021)
We investigated Nigerian’s post-colonial resurgences of internal boundary and religious conflicts that have bedeviled the country since independence based on the problems of national integration in post-colonial Nigeria. It argued that resurgences of internal boundary and religious conflicts in the country since liberation in 1960 are crops of expansionism in the sense that colonialism, while the postcolonial state could not avert the ills of colonial rule but rather re-invented the foreign strategy of division and law. It also argues that the scuffles for control of the naturally found resources in the localities are a result of “oppression, marginalization and government influence, uneven distribution of wealth and resources, nepotism and socio-religious bigotry,” which have over the years led religious groups, communities, local governments and States to a long-drawn-out deadly boundary and religious conflicts. The objective of this research is not only aim at highlighting the impact of internal boundary and religious conflicts on the Nigerian federation but also to draw the attention of Nigerian policymakers and researchers to the “neglect” of these issues, which have pitted groups between and even within states in the country, with deadly consequences, thereby questioning the principle of national integration and its essence in Nigeria. The methodology used in this research is the secondary source that has to do with published and unpublished works on the internal boundary, religious conflicts, and national integration. The paper submits that the existence of different natural resources found within the country should not always lead to the internal boundary and religious conflicts but cooperation amongst the people.